Wind loading of structures - Holmes, John D., 1942- (CRC Press, 2015)
"Preface to the third edition Since the publication of the second edition of Wind Loading of Structures, strong windstorms have continued to occur at frequent intervals across the world: Hurricane 'Sandy' (2012) on the east coast of the United States, and Typhoon 'Haiyan' in the Philippines (2014) are just two recent damaging examples. Whether there is an increase in the number and/or intensity of these events as a result of global warming is not yet established, but it is certain that the number of structures exposed to the loads imparted by strong winds has escalated, and there is a strong demand by structural engineers worldwide for guidance on practical methods for the design of wind actions, with the appropriate balance between safety and economy. In the same period, the largest structures have become even more wind sensitive. For example, the current world's tallest building (Burj Khalifa) is now nearly twice the height of the tallest building in 2007 (Taipei 101), requiring a large amount of wind engineering in the design process. In the last 7 years, there has also been an explosion in the number of research papers on the topic of wind loading of structures through reports, conference presentations and journal papers, so that it is now virtually impossible for even a specialist to keep up with the output. However, I have endeavoured to expand parts of the book with new information, when it is of practical value to practising engineers, or if it provides new understanding of the basic phenomena involved"--